Financiamiento de la salud en Chile: análisis histórico y de largo plazo del sistema segmentado, 1981-2024. - Matus-López, Mauricio; Cid Pedraza, Camilo (Cuadernos Médico Sociales, 2026)
The objective of this article is to present the results of reconstructing the historical series of health expenditure in Chile from the creation of the segmented model in 1981 to 2024 and to briefly analyze its evolution in a historical context. To achieve this, data were collected and digitized from primary sources: Statistical Bulletins and Public Accounts of FONASA (1989-2016; 2020-2024), Statistical Series of the Isapre System (SUPER, 1990-2024), and Public Finance Statistics (DIPRES, 2004-2025). The results show accelerated growth in private spending until the 1990s, followed by a sustained increase in public health expenditure associated with higher fiscal contributions and mandatory contributions. However, the long-term analysis reveals periods of slowdown in public spending coinciding with the expansion of private infrastructure, highlighting the persistence of segmented and unequal financing. The trajectory of health expenditure in Chile presents significant variations in proportions and rhythms, conditioned by political